Melonite from Kingash and Kuskanak, Eastern Sayans, Russia, and the extent of Bi-for-Te substitution in melonite and synthetic Ni(Te, Bi)2–x. (2nd January 2018) - Barkov, Andrei Y.; Shvedov, Gennadiy I.; Flemming, Roberta L.; Vymazalová, Anna; Martin, Robert F.
Abstract: We describe occurrences of palladoan melonite in intimate intergrowths with cobaltite-gersdorffite from the Neoproterozoic dunite-wehrlite-gabbro complexes of Kingash and Kuskanak, Eastern Sayans, Russia. The observed compositional trends of melonite are consistent with the overallvariations examined on the basis of numerous literature sources. The levels of Bi in NiTe2 are normally limited to ≤0.25 Bi atoms per formula unit (apfu), under natural conditions. Greater levels (≤0.5 Bi apfu) are associated with the (Pd + Pt) enrichment in the palladoanvarieties. The telluride–sulfarsenide intergrowths probably formed at Kingash and Kuskanak late in the crystallization history of the ore zones, from microdroplets of residual melt rich in semimetals (Te, Bi, As) and noble metals (Pd and Ag), below the solidus of the enclosing gabbroicrocks and within a narrow range of temperatures (500–550°C). On the basis of our observations made on specimens of melonite and synthetic Ni(Te, Bi)2–x (x = 0.6), we infer that the limit of incorporation of Bi into a melonitetype phase is ≤0.5 Bi apfu.